Epigenetic inactivation of endothelin‐2 and endothelin‐3 in colon cancer1. Issue 5 (24th August 2012) - Wang, Rong; Löhr, Christiane V.; Fischer, Kay; Dashwood, W. Mohaiza; Greenwood, Jeffrey A.; Ho, Emily; Williams, David E.; Ashktorab, Hassan; Dashwood, Michael R.; Dashwood, Roderick H.
Abstract Endothelin‐1 (ET‐1) and its receptors are overexpressed in human cancers, but much less is known about the roles of ET‐2 and ET‐3 in cancer etiology. We sought to examine human and rat colon tumors for dysregulation of ET‐2 and ET‐3 expression and determine the underlying mechanisms. Human primary colon cancers and carcinogen‐induced rat colon tumors were subjected to real‐time RT‐PCR, immunoblotting and immunohistochemistry; EDN2 and EDN3 genes were examined by methylation‐specific PCR, bisulfite sequencing and pyrosequencing; and forced expression of ET‐2 and ET‐3 was conducted in human colon cancer cells followed by real‐time cell migration and invasion assays. Rat and human colon tumors had markedly reduced expression of ET‐2 and ET‐3 mRNA and protein compared with matched controls. Mechanistic studies revealed hypermethylation of EDN2 and EDN3 genes in human primary colon cancers and in a panel of human colon cancer cell lines. Forced expression of ET‐2 and ET‐3 attenuated significantly the migration and invasion of human colon cancer cells. We conclude that epigenetic inactivation of ET‐2 and ET‐3 occurs frequently in both rat and human colon cancers. Current therapeutic strategies target overexpressed members of the ET axis via small molecule inhibitors and receptor antagonists, but this work supports a complementary approach based on the re‐expression of ET‐2 and ET‐3 as natural antagonists of ET‐1 in colon cancer.